Education And Training: Triangulation Of The Foundations Of Maritime Safety Improvement Policies - Lamatokan, Sisca Cletus; Suryadi, Suryadi; Cahyana, Ucu (International Journal of Business, Law, and Education, 2024)
Maritime safety has been a primary concern for the Indonesian government since 1978 through the Minister of Transportation Decision No. KM. 53/OT/PHB-78. The formulation of Maritime Safety Improvement policies is carried out by identifying the phenomena regarding the urgency of improving maritime safety for the sustainability of both national and international shipping, grounded in legal products. The policy foundation is derived from three aspects: Maritime Safety Aspect, Manpower Management Aspect, and Education and Training Aspect. The result of this policy formulation gives birth to a new policy product, namely the Functional Sea Transportation Technical Training implemented by the Sea Transportation Education and Training Center (BP2TL). This research is a Policy Evaluation study using a qualitative approach by exploring three research focuses: the policy program's background, program objectives, and program targets. Data acquisition for the research is done through interview techniques, documentary studies, and literature reviews.